Determination of Spatial and Temporal distribution of MS Patients in Kerman - Rasa Raeisi; MohammadReza Noghsan Mohammadi; Seyed Ali Almodaresi (Kerman University of Medical Sciences, 2017)
Background & Objectives: Multiple sclerosis is an autoimmune disease causing disability in . The environmental factors play an important role in disease spread and since youths are affected more, this disease is of a great importance. As the incidence of this disease is not the same around the world, through using geographic information system, the spatial and descriptive data can be used to create maps, tables, and charts for data analysis and preventing the progression of the disease. Methods: In this descriptive study, 1200 Multiple sclerosis patients in Kerman province between 1987 and 2015 were surveyed. After collecting data and spatial data, the geographical distribution map of the disease was prepared. In this base, first, the points were inserted in the Google Earth and then, the locations of patients' accumulation were found by analyzing the hot spots. Results: According to the results, the majority of patients were habitants of the margin of Kerman and in the Salsabil area. The lowest numbers of patients were in Kuhbanan and Kahnouj. Women were affected 3.5 times more than men and the age group of 20 to 30 years old had the highest rate of this disease. Conclusion: Improving urban infrastructures, reducing construction density, controlling traffic problems, and improving the quality of urban life can improve the health of patients. Keywords: MS Disease, Geographical Distribution Map, Geographic Information System, Kerman Province Citation: Raeisi R, Noghsan Mohammadi MR, Almodaresi SA. The Geographical Distribution of Multiple Sclerosis patients in Kerman City by using Geographic Information System. Journal of Health Based Research 2017; 3(3): 217-226.